Additive manufacture with copper and silver nanoparticles - Pervan, David (2020)
Additive Manufacturing (AM) of electrically conductive copper (Cu) parts is of significant research interested. Cu’s high thermal and electrical conductivity combined with its relative abundance and low price makes it an ideal material for thermal and electrical devices. Unlike conventional subtractive manufacturing processes, AM is capable of producing highly geometrically complex parts which is beneficial for many thermal and electrical devices applications. To date there are only capital and energy intensive AM processes which can produce macro-scale Cu parts exist. There is no low-energy process capable of additively manufacturing electrically conductive copper (Cu) microparts. Additively manufactured Cu microparts have potential applications such as microchips, electronic microdevices, medical devices, microfluidic devices, and micro-optical systems. This thesis aims to lay the groundwork for a novel low-power AM process, capable of producing electrically conductive Cu microparts from nanoparticle feedstock in an air environment.